Digital Marketing Untuk Meningkatkan Umkm Penjualan Es Teh Anak Rantau Kota Pekanbaru - Dwi Anindya Harimurti; Noprieka Suriadiman; Andry Andry (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2024)
Digital literacy refers to a person's ability to use, understand, and participate in the digital environment effectively. The development of information technology has changed the scope of the marketing world in recent years. Marketing communication methods that were previously traditional and conventional have now been integrated into the digital world. Digital marketing has become one of the media that is often used by business people because of the new ability of consumers to follow the flow of digitalization, several companies are gradually starting to abandon conventional marketing models and switch to modern marketing.The development of information technology is growing rapidly. Some activities of Micro, Small and Medium Enterprises (MSMEs) utilize information technology to run their business. One of them is the MSME Anak Rantau Iced Tea. Through the community service team, training on digital marketing was carried out as an effort to develop the Iced Tea Children of Rantau MSMEs The results of this activity showed that business actors participated in the training activities carefully. This can be seen from the enthusiasm of the actors in understanding marketing digitalization